(1087) Theoretical Comparison, Computational and Practical Experience with Some Transportation Type Algorithms/ المقارنة النظرية، والخبرة الحاسوبية والعملية مع بعض خوارزميات انوع النقل - A., . N. ElShafei.; K., B. Haley. (INP, 2025)
11 P.